Islam: Local and Global Challenges (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2011)
Indeed, in maintaining their local values when faced with global challenges, Muslims, as a social entity, and Islam, as a set of dogma, have given birth to new phenomena, e.g. new interpretation of Islam within a new context. Additionally, this era of globalization has led religions, including Islam, to renew their gambit to cope reality, e.g. in the practical life (sociological, political, economical and anthropological aspects), intellectual endeavors (philosophical and theological aspects), and in the renewal of dogmatic teachings (hermeneutical aspects).